2023
DOI: 10.1073/pnas.2215371120
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E4 has extensive conformational heterogeneity in lipid-free and lipid-bound forms

Abstract: The ε4-allele variant of apolipoprotein E (ApoE4) is the strongest genetic risk factor for Alzheimer’s disease, although it only differs from its neutral counterpart ApoE3 by a single amino acid substitution. While ApoE4 influences the formation of plaques and neurofibrillary tangles, the structural determinants of pathogenicity remain undetermined due to limited structural information. Previous studies have led to conflicting models of the C-terminal region positioning with respect to the N-terminal domain ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…All single-molecule FRET experiments have been performed in a 50 mM N -(2-hydroxyethyl)­piperazine- N ′-ethanesulfonic acid (HEPES) buffer pH 7.4 at a temperature of 23 °C, unless differently specified, with addition of 200 mM β-mercaptoethanol and 0.001% v/v Tween 20. Single-molecule measurements were performed on a modified PicoQuant MT200, as previously described. , Volume fractions of PEG solutions have been computed by converting from the weight/volume (w/v) fraction using the density of PEG molecules, as previously reported. , Further experimental and theoretical details are reported in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…All single-molecule FRET experiments have been performed in a 50 mM N -(2-hydroxyethyl)­piperazine- N ′-ethanesulfonic acid (HEPES) buffer pH 7.4 at a temperature of 23 °C, unless differently specified, with addition of 200 mM β-mercaptoethanol and 0.001% v/v Tween 20. Single-molecule measurements were performed on a modified PicoQuant MT200, as previously described. , Volume fractions of PEG solutions have been computed by converting from the weight/volume (w/v) fraction using the density of PEG molecules, as previously reported. , Further experimental and theoretical details are reported in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…These results also showed that an interaction with intracellular ApoE was much more effective in altering the lifetime. This is possibly due to the different lipidation states of the recombinant ApoE used for the in vitro experiments, which have been known to result in a conformational difference. , A corresponding oligomer distribution of the ApoE4 incubated RAβ oligomers showed similarity to the RN46A extracted oligomers (Figure B). Our results showed that human ApoE4 could produce short-lifetime Aβ oligomer species in vitro.…”
Section: Resultsmentioning
confidence: 98%
“…A plausible interaction of ApoE with Aβ has been a focus of multiple solution-state and intracellular studies(7). However, these have produced inconsistent results(8,9), possibly due to variations in the lipidation state of ApoE(10) and the oligomeric state of Aβ between different experiments. Strong evidence for a direct interaction of ApoE with Aβ comes from peptides that mimic stretches of Aβ and can block such interactions in vitro , and can also significantly reduce Aβ toxicity in cells(11,12).…”
Section: Main Textmentioning
confidence: 99%
“… A) Schematic representation of the experiment. B) Fluorescence Intensity, lifetime, and average lifetime distribution of RΑβ oligomers in astrocytes (1,2, and 3), cortical neurons (4,5, and 6), RN46A cells (7,8,9), and HeLa cells (10, 11, and 12). The average lifetime distribution is fitted using three Gaussians (description in SI 5, figure S3 ), representing short, intermediate and long lifetimes, with their peaks allowed to vary within a certain range.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation